Critical Synthesis Package: Competency-Based Test of Inpatient Geriatric Management (CTIGM) for Residents and Medical Students - Huai Cheng; Michelle Yoon (Association of American Medical Colleges, 2014)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education of the Competency-Based Test of Inpatient Geriatric Management for Residents and Medical Students (CTIGM), and (2) a copy of the CTIGM and the scoring instructions developed by Ethan Cumbler, MD. The CTIGM was originally designed to assess performance of internal medicine residents and medical students who are rotated in inpatient geriatric service. It covers seven geriatrics and three hospital medicine competencies for residents. It also covers five minimum geriatric competencies for medical students. The CTIGM is well aligned with the two ACGME core competencies of patient care and medical knowledge. It uses a standardized constructed-response format and is administered to residents and third-year medical students who are required to write admission orders based on a real-life case of hospitalized older patient. The trainees' admission orders will be scored from 0 to 100 using ten pre-defined answers and a scoring system. The CTIGM is simple to administer and grade. It has good face validity. However, internal consistency using Cronbach's statistics, test-retest reliability among trainees, inter-or intra- correlations of scoring among faculty, and concurrent and predictive validity of the CTIGM to other instruments were not tested. Given that, we would not endorse the CTIGM. However, we recommend that health care educators use the CTIGM as a template to develop similar instruments to assess geriatrics and hospital medicine competencies for internal medicine residents and medical students, as well as to establish reliability and validity.